Effect of fascia in rehabilitation and healing the muscles behind the thigh for football players - Darwish Ahmed, Hossam (International Journal of Psychosocial Rehabilitation, 2020)
Fascia is a term that is gaining more attention in the sport medicine field for being a major contributor to soft tissue injuries and pain. Fascia is not easily seen on MRI scans, X-rays or ultrasounds, which is why it has often been overlooked when treating injuries. Fascia plays a significant role in many people with longstanding injuries. Common examples include low back pain, rotator cuff injuries, tennis elbow, shin splints and frozen shoulder.